Treading water: why organisations are making no progress on cyber security. Issue 11 (November 2019) - Aleem, Azeem
Abstract : Business leaders are acutely aware of the importance of cyber security and recognise the pressing need to address it, according to a recent report. 1 However, many of the organisations surveyed as part of the research are failing to make any headway in their efforts to protect their data, infrastructure, assets, people and customers from cyber attacks.